Quantitative Membrane Protein Expression at the Blood–Brain Barrier of Adult and Younger Cynomolgus Monkeys - Ito, Katsuaki; Uchida, Yasuo; Ohtsuki, Sumio; Aizawa, Sanshiro; Kawakami, Hirotaka; Katsukura, Yuki; Kamiie, Junichi; Terasaki, Tetsuya (Journal of pharmaceutical sciences, 2011)
Cynomolgus monkey has been used as a model for the prediction of drug disposition in human brain. The purpose of this study was to clarify protein expression levels of membrane proteins affecting drug distribution to brain, such as transporters, receptors, and junctional proteins, in cynomolgus monkey brain microvessels by using liquid chromatography tandem mass spectrometory. In adult monkeys, three ATP-binding cassette transporters (multidrug resistance 1 (MDR1), breast cancer resistance protein (BCRP), and multidrug resistance protein 4 (MRP4)), six solute carrier transporters (glucose transporter 1 (GLUT1), GLUT3/14, monocarboxylate transporter 1 (MCT1), MCT8, organic anion transporting polypeptide 1A2, and equilibrative nucleoside tranporter 1), two junctional proteins (claudin-5 and vascular endothelial cadherin), and two receptors (insulin receptor and low-density lipoprotein receptor-related protein 1) were detected. Comparison of the expression levels with those in mouse, which we reported previously, revealed a pronounced species difference. BCRP expression in monkey was greater by 3.52-fold than that in mouse, whereas MDR1 and MRP4 expression levels in monkey were lower by 0.304- and 0.180-fold, respectively, than that in mouse. This study also investigated the developmental changes in expression of membrane proteins in neonate and child monkeys. Expression of MDR1 was similar in neonate and adult monkeys, whereas in rat, P-glycoprotein expression was reported to be significantly lower in brain microvessels of neonate as compared with adult rat. These results will be helpful to understand and predict brain concentrations of drugs in different species and at different ages of primates. © 2011 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 100:3939–3950, 2011